Eficacia de la fiscalización ambiental de los gobiernos regionales a la pequeña minería y minería artesanal y la conservación del ambiente 2019 – 2020 - Ulloa Rodríguez, Yerlin Alvarito (2022)
Since time immemorial, mining activity has become a fundamental pillar for the development and progress of various towns and cities around the world; however, its bad practice, mainly related to informal activity, has been causing a number of social and environmental problems; that added to the fact of the existence of legal gaps and technical deficiency in the current regulations, delay or prevent the normal fulfillment of the functions of environmental control throughout the country. Given this, the present investigation focused on determining the effectiveness of the environmental control of the Regional Governments to small-scale mining and artisanal mining and its implication in the conservation of the environment. For this, the reports of the supervisions carried out during the 2019 and 2020 period of the 25 Decentralized Offices of the Environmental Assessment and Enforcement Agency were collected, the same ones that after being ordered and classified by the Regional Government, were grouped into 06 components, taking as reference the methodology developed by OEFA; All of this allowed the elaboration of the efficiency index of the environmental control activities of these regional governments and their incidence in environmental deterioration. Information that was later complemented with literature from scientific journals, books, theses and other updated bibliographic sources; in order to allow reliable results to be captured through statistical tables and graphs. It is concluded that there is a low performance in the environmental control of the Regional Governments to small-scale mining and artisanal mining, as a result of the non-compliance of the 6 components used for evaluation, supervision, control and qualification of the environmental obligations of the environmental control entities. regional.